ANALYSIS OF CULTURE AND SOCIAL CHANGE OF BADUY LUAR TRIBE IN LEBAK BANTEN - Anisa Pitria Sari; Siti Rahmawati; Putri Malia; Eneng Liah Khoiriyah (Media Inovasi Pendidikan dan Publikasi, 2023)
Indonesia has a variety of rich and unique cultures and a large number of ethnic groups. Outer Baduy is one of the tribes in Indonesia. Outer Baduy is generally more open to cultural influences from outside and has been influenced by modern culture. This is inseparable from the development of the times which causes some social changes that occur in the Baduy community. This research uses ethnographic method based on qualitative approach. This research was conducted to find out whether there was a change in the baduy luar where we know that the baduy tribe is very closed and still traditional, when conducting an analysis we know that there have been more modern changes in the baduy luar, such as in economic and social terms, even so their culture is still very thick.